The Diocese of Muccurum (Ecclesia Muccuritana) in Dalmatia - Škegro, Ante (Arheološki vestnik, 2008)
During the Second Salonitan council held on the 23rd of May 533, among other things, three new dioceses were established with their seats at Sarsenterum,Muccurum and Ludrum. Many authors have dealt with the question of the location of these places, the entities included in the dioceses, as well as the ju-risdiction of their bishops. However, many fundamental issues concerning them are still disputable, due to the many mistakes and the corrupted Latin in which the documents of the council were written, since this is the only document in which these dioceses were mentioned. The diocese with its seat at Muccurumhad all the characteristics of a rural diocese. The jurisdiction of its bishop spread, quite likely, from the southeastern parts of Mosor Mountain and Poljica to the Neretvan marshes and the central Dalmatian islands of Brač, Hvar, and Vis (possibly also Korčula), as well as from the northwestern parts of the Pelješac peninsula to the area of Imotski-Bekija